10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Antimicrobial resistance (AMR) represents a growing global public health threat, undermining therapeutic efficacy and disproportionately affecting vulnerable populations. In Ecuador, the situation is exacerbated by weak surveillance systems and fragmentation among the human, animal, and environmental health sectors. This study analyzes current national approaches that address AMR in Ecuador from a One Health (OH) perspective, with an emphasis on governance, public policy, health infrastructure, and equity. A qualitative approach was employed combining document review, scientific literature analysis, and semi-structured interviews with key informants (KIs) engaged across all OH sectors. Findings reveal structural barriers, including lack of institutionalization of the OH strategy, limited funding for the health system, weak intersectoral coordination, low community awareness, and the absence of equity-oriented policies. In conclusion, the results highlight the urgent need to strengthen the governance of antimicrobial stewardship in Ecuador through strategies that are contextually adapted, aligned with international recommendations, and grounded in a comprehensive multisectoral approach.